Examining acculturative stress among international students in Ghana using an interpretative phenomenological approach. Unpacking the social support systems. - Kwasi Gyasi-Gyamerah; Joseph Osafo; Angela Anarfi Gyasi-Gyamerah; Evans Sakyi Boadu (PLoS ONE)
Acculturation, a cultural and psychological process, can cause stress for international students studying in Ghanaian universities. This paper examined the challenges faced by these students, highlighting the many obstacles they face on campus and throughout the country, and the social support systems available to them. Using the interpretative phenomenological approach (IPA), rooted in acculturative stress concepts this paper found that international students often find life challenging and frustrating, regardless of their continent of origin. The paper revealed that university administrators and faculties do not adequately support international students, and self-efficacy is insufficient in coping with acculturative stress. Financial concerns, being unrealistically perceived as affluent, abrupt academic schedule changes, weather conditions, and frequent marriage proposals were significant sources of stress. This paper observed that international students in Ghana enjoy immediate and long-term advantages such as bilingualism, cultural awareness, intercultural understanding, high-status recognition, and easier employment in their home countries. The paper concludes that international students often struggle to adjust to Ghana's new sociocultural and academic environment albeit there are some advantages. The findings of this study can help offices of international student affairs and student exchange organizations on university campuses in Ghana, thus, providing tailored counselling services to students in vulnerable groups.